Why does classical reception need disability studies? - Silverblank, H; Ward, M (Oxford University Press, 2020)
Many of the ableist tropes around disability and disabled people in the modern world find their antecedents in ancient mythology and its reception, but the seemingly ‘traditional’ nature of these harmful tropes and reflexes of storytelling is not established by accident or in the absence of readers. We argue here that classical reception needs to look to disability studies for a methodology that will allow the field to begin to theorize the role of the reader in the perpetuation of the ideology of ableism and ideas of bodily normativity. The field of classical reception studies engages in the process of investigating how the ‘traditional’ comes to be accepted as pre-existing; as such, it is vital that classical reception look to disability studies for the tools with which to lay bare the ways in which the apparatus of ableism comes to seem traditional. This article sets out some strategies for bringing classical reception and disability studies together with the aim of developing a more critical philology, an ethically-invested method for doing classical reception, and the theoretical and practical tools to create a more inclusive field. In short, this article makes the case for ‘cripping’ classical reception studies.